Decaying shock studies of phase transitions in MgO‐SiO2 systems: Implications for the super‐Earths' interiors. Issue 18 (28th September 2016) - Bolis, R. M.; Morard, G.; Vinci, T.; Ravasio, A.; Bambrink, E.; Guarguaglini, M.; Koenig, M.; Musella, R.; Remus, F.; Bouchet, J.; Ozaki, N.; Miyanishi, K.; et al.
Abstract: We report an experimental study of the phase diagrams of MgO, MgSiO3, and Mg2 SiO4 at high pressures. We measured the shock compression response, including pressure‐temperature Hugoniot curves of MgO, MgSiO3, and Mg2 SiO4 between 0.2–1.2 TPa, 0.12–0.5 TPa, and 0.2–0.85 TPa, respectively, using laser‐driven decaying shocks. A melting signature has been observed in MgO at 0.47 ± 0.04 TPa and 9860 ± 810 K, while no such phase changes were observed either in MgSiO3 or in Mg2 SiO4 . Increases of reflectivity of MgO, MgSiO3, and Mg2 SiO4 liquids have been detected above 0.55 TPa (12760 K), 0.15 TPa (7540 K), 0.2 TPa (5800 K), respectively. In contrast to SiO2, melting and metallization of these compounds do not coincide, implying the presence of poorly electrically conducting liquids close to the melting lines. This has important implications for the generation of dynamos in super‐Earth's mantles. Key Points: Magnesium oxides phase diagrams investigated along the Hugoniots between 0.2 and 1.2 TPa with decaying shocks and optical diagnostics New MgO experimental melting point proposed at 0.47 ± 0.04 TPa and 9860 ± 810 K No evidences of phase transition have been found for MgSiO3 and Mg2 SiO4 between 0.12–0.5 TPa and 0.2–0.85 TPa, respectively